Short-term outcome of metabolic surgery versus intensive medical therapy among obese type 2 diabetics: a quasi-experimental study - Zahra Raza; Muhammad Burhan Ul Haq; Tashfeen Imtiaz; Muhammad Adnan Khokhar; Aatif Inam (Journal of the Pakistan Medical Association, 2025)
Objective: To compare the short-term outcomes of metabolic surgery and intensive medical therapy in the management of diabetes mellitus among obese persons with type 2 diabetes mellitus. Methods: The quasi-experimental study was conducted at the Pakistan Institute of Medical Sciences, Islamabad, Pakistan, from March 2018 to February 2019, and comprised obese type 2 diabetes mellitus patients of either gender aged 20-65 years. Those undergoing metabolic and bariatric surgery were assigned group A, while those undergoing intensive medical therapy formed control group B. All patients were followed up for 6 months to monitor their metabolic profile, including body mass index, glycosylated haemoglobin and fasting plasma glucose. Data was analysed using SPSS 20. Results: Of the 72 patients, 36(50%) were in group A; 23(63.9%) females and 13(36.1%) males with mean age 41.2 years (SD± 10.2). The remaining 36(50%) patients were in group B; 22(61.1%) males and 14(38.9%) females with mean age 42.5 years (SD ± 10.6) (p>0.05). At 6 months, mean body mass index, glycosylated haemoglobin and fasting plasma glucose values were significantly lower in group A compared to group B (p<0.001). There were 33(91.7%) patients in group A with remission of diabetes compared to 1(2.8%) patient in group B (p<0.001). Conclusion: Bariatric surgery was found to produce a good early outcome in the management of diabetes in the obese population, leading to remission post-surgery. Key Words: Bariatric surgery, Metabolic surgery, Obese T2DM, Diabetes remission, Diabetes.